Transforming Agricultural Living Labs into Lighthouses Contributing to Sustainable Development as Defined by the UN-SDGs - Jan Adriaan Reijneveld; Mark Geling; Edwin Geling; Johan Bouma (Soil Systems)
The UN Sustainable Development Goals (SDGs) were intended to be met by 2030, but recent reviews show that this will not be achieved, and recommendations have been made to heads of state, governments, the international community, and member states to strengthen their efforts. Focusing on agriculture, we argue that a bottom-up effort is also needed in living labs, one that truly involves farmers, as they are now confused about, and resistant to, top-down rules and regulations. To provide clarity, we suggest the following: (i) selecting key SDGs by considering the proportionality principle, and (ii) defining ecosystem services in terms of indicators and thresholds for income, the production of healthy food, the protection of water quality, contribution to energy preservation and climate mitigation, and the protection of life on land, including soil health (SDGs 1, 2, 3, 6, 7, 13, 15). Indicators and thresholds have to be clear and measurable and achievable within reasonable costs. The introduction of innovative sensing techniques allowed the rapid generation of relevant soil data in the field of living labs. When meeting all thresholds, a “lighthouse” is established to act as an inspiring example for farmers with similar soils in a given region. Policies should focus on achieving thresholds of a set of indicators rather than on prescribing certain top-down management measures.